Sanitarismo e planejamento urbano: a trajetória das propostas urbanísticas para Natal entre 1935 e 1969 - Dantas, Ana Caroline de Carvalho Lopes (2003)
The Escritório Saturnino de Brito (Saturnino de Brito Office), created in 1920 under the sanitaristic guidance of the engineer Saturnino de Brito, has a vast record of works throughout the whole national territory, even after the death of its founder, in 1929 at which point his son, and also engineer, Saturnino de Brito Filho, assumed the head of the company , with a compromise to continue his father s work and assure his administrative, technical and urbanistic principles up until the early 1980s, when that institution came to an end. The scarcity of theorical studies about this Office, alongside the importance of the contributions it made in countless cities, oriented the focus of this study on its performance in Natal, where it remained from 1935 to 1969, designing, executing and managing sanitationist works and the services associated with them and going through several political, economical, social, cultural and urbanistic contexts periodicized in this work into three moments. Thus, it is intended to analyze how the Saturnino de Brito Office behaved and adapted itself to the conjunctural changes that unfolded into each of these moments, and more specifically, to observe the forms of intervention adopted the principles, the instruments and the scope aiming to verify the transition of the sanitaristic set of urbanistic ideas into the urban planning as a development strategy on a local level